A critical review on saline wastewater treatment by membrane bioreactor (MBR) from a microbial perspective. (April 2019) - Tan, Xu; Acquah, Isaac; Liu, Hanzhe; Li, Weiguo; Tan, Songwen
Abstract: This work has reviewed from a microbial perspective and listed the typical studies on MBR techniques for saline wastewater treatments. When the salinity of influent is lower than 10 g/L NaCl, conventional MBR can be easily applied with adjusted operating conditions. For better biodegradation and anti-fouling ability at higher salinities (10–100 g/L), modified and hybrid MBR systems may need to be wisely designed according to the change in the microbial community and contents of EPS/SMP. To treat hypersaline wastewaters with salinities of up to 100 g/L NaCl, inoculation of halophilic bacteria has been applied in MBR works. Microbial community structures in some typical works have been discussed from a microbial perspective to benefit the identification and isolation of halophilic bacteria for future works. The following aspects are also suggested in future MBR research for saline wastewater treatment: (1) The structure design of MBR and the manufacture of advanced membranes; (2) The maintenance of the microbial biodiversity for anti-membrane fouling; (3) The metabolic mechanism for halophilic (or salt-tolerant) microorganisms against salinity shocks; (4) The revolution stage and process of microorganisms during saline wastewater treatment in MBR; (5) The effects of characteristics (cell structure, shape and metabolic pathways) of microorganisms on the salt tolerance; (6) Applying halophilic microorganisms for salinities over 150 g/L NaCl. Graphical abstract: Image 106 Highlights: Conventional MBR has been used for salinity below 10 g/L. Inoculation of halophilic microorganisms can be applied for salinity up to 150 g/L. Typical halophilic microorganisms and MBR-hybrid systems are reviewed. Membrane biofouling is discussed from a microbial perspective. Tendency for possible future works is suggested.